2018
DOI: 10.3311/ppci.11411
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Portland Cement Mortar with Substitutions of Natural and Expanded Perlite

Abstract: The present research deals with the feasibility of using hightemperature pozzolans such as Natural Perlite (NP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…4), since now the CELU+PEM mixture shows a behavior slightly above the control at the ages 7 and 14 days and then decreases a little at the age of 28 days, reach again the strength of the control mixture in the last age. The better performance of the CELU+PEM mixture can be attributed to the particle size of one of the two components, in particular to the PEM, since a previous research reported an increase in physical solicitation using substitutions of PE with particle size less than 44μm [15]. The test results of UPV and electrical resistivity, in which it can be seen as the mixture CELU+PEM presents a significant increase at the age of 28 and 14 days respectively, spreading the control both the CELU mixture are presented in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…4), since now the CELU+PEM mixture shows a behavior slightly above the control at the ages 7 and 14 days and then decreases a little at the age of 28 days, reach again the strength of the control mixture in the last age. The better performance of the CELU+PEM mixture can be attributed to the particle size of one of the two components, in particular to the PEM, since a previous research reported an increase in physical solicitation using substitutions of PE with particle size less than 44μm [15]. The test results of UPV and electrical resistivity, in which it can be seen as the mixture CELU+PEM presents a significant increase at the age of 28 and 14 days respectively, spreading the control both the CELU mixture are presented in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Clays (most well-known is metakaolin) are an effective replacement material after calcination for blended cement production [9,10]. Moreover, there are also studies on the use of binary or ternary blended cements such as metakaolin-limestone [11][12][13], fly ash-limestone [14][15][16][17]. The results of studies conducted on calcined clay blended cements and binary or ternary blended cements that contains synergic reactions are quite pleasing.…”
Section: Introductionmentioning
confidence: 99%